2013
DOI: 10.1086/669132
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Causes ofDiporeiaDecline in the Great Lakes via Metabolomics: Physiological Responses after Exposure to Different Stressors

Abstract: The benthic macroinvertebrate Diporeia spp. have been extirpated from many areas of the Laurentian Great Lakes, but the mechanisms underlying such declines are not fully understood. Diporeia declines coinciding with the invasion of exotic dreissenid mussels (zebra and quagga) have led to the hypothesis that Diporeia declines are a result of decreased food availability from increasing competition with dreissenids for diatoms. There is additional evidence that Diporeia are negatively affected when in close proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Barbiero et al (2011) reported declining numbers of Diporeia in Lake Huron despite much lower abundances of Mussels there, and Mussels coexist with Diporeia in several smaller lakes (Dermott et al, 2005b;Watkins et al, 2012), suggesting that Dreissenids may not be directly implicated in the Diporeia decline. Interestingly, Diporeia from declining populations do not show decreased condition (Nalepa et al, 2009a), and stressors applied to the animals give the same metabolic response regardless of the presence of Quagga Mussels (Maity et al 2013). Furthermore, the decline in the spring bloom observed in Lake Michigan (Mida et al, 2010;Vanderploeg et al, 2010;Kerfoot et al, 2010) did not occur in Lake Ontario, even though Diporeia declined in both lakes .…”
Section: Discussionmentioning
confidence: 95%
“…Barbiero et al (2011) reported declining numbers of Diporeia in Lake Huron despite much lower abundances of Mussels there, and Mussels coexist with Diporeia in several smaller lakes (Dermott et al, 2005b;Watkins et al, 2012), suggesting that Dreissenids may not be directly implicated in the Diporeia decline. Interestingly, Diporeia from declining populations do not show decreased condition (Nalepa et al, 2009a), and stressors applied to the animals give the same metabolic response regardless of the presence of Quagga Mussels (Maity et al 2013). Furthermore, the decline in the spring bloom observed in Lake Michigan (Mida et al, 2010;Vanderploeg et al, 2010;Kerfoot et al, 2010) did not occur in Lake Ontario, even though Diporeia declined in both lakes .…”
Section: Discussionmentioning
confidence: 95%
“…(C) Moult stages and main modifications of exoskeleton and growth (non-proportional presentation with respect to duration of each period). Abbreviations: CCAP, crustacean cardioactive peptide; CHH, crustacean hyperglycemic hormone; EcR, ecdysteroid receptor; MF, methyl farnesoate; MIH, moult-inhibiting hormone; MOIH, mandibular organ-inhibiting hormone; 20E, 20-hydroxyecdysone; PoA, ponasterone (A) 1 (70); 2 (71); 3 (72); 4 (73); 5 (74); 6 (75); 7 (76); 8 (77); 9 (78); 10 (79).…”
Section: Neuro-endocrine Regulationmentioning
confidence: 99%
“…This ecological and economical wealth is, however, endangered by habitat loss, climate change, pollution, overexploitation, invasive species and other anthropogenic stressors ( 8 ). In the early nineties, drastic declines of amphipods were reported in some of the Great Lakes ( 9 , 10 ). Similarly, populations of the amphipod Gammarus lacustris significantly declined in the Selenga River delta, the main tributary to Lake Baikal ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amphipoda is a well-established and long-recognized indicator of good ecosystem health for assessing the ecological status of aquatic environments (Dauvin, 2018). In particular, pontoporeiid species are known to be highly sensitive to climate warming and different local environmental disturbances like eutrophication, pollution, acidification (Demandt et al, 2012;Goedkoop, 2006;Maity et al, 2013). In the Baltic Sea, M. affinis is used as a bioindicator to monitor benthic community ecology and biological effects of contaminants (Löf et al, 2016;Sundelin & Eriksson Wiklund, 1998).…”
Section: Introductionmentioning
confidence: 99%